2002
DOI: 10.1577/1548-8659(2002)131<0698:fibtrs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Brown Trout Reproductive Success in Ozark Tailwater Rivers

Abstract: The reproductive success of brown trout Salmo trutta in White River, Arkansas, tailwater reaches is highly variable, resulting in the need for supplemental stocking. A better understanding of the physical and biotic factors affecting reproduction and survival would enhance the contribution of wild fish. We compared fecundity, reproductive chronology, physical habitat, water quality, trout density, food availability, diet, predation, and competitive interactions among four tailwater reaches to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 66 publications
4
26
1
Order By: Relevance
“…The positive selection by brown trout for Gammarus and Physella, and avoidance of Dipterans, is consistent with studies in other regions (Cada, Loar, Sale 1987;Pender and Kwak 2002;Fochetti et al 2003;Johnson et al 2007;Sanchez-Hernandez et al 2011), although Pender and Kwak (2002) found positive selection for Chironomidae among age-0 trout. Physella did not constitute a high proportion of either prey availability or prey consumed, but brown trout consistently favored Physella in the benthos and drift.…”
Section: Broad Patternssupporting
confidence: 89%
“…The positive selection by brown trout for Gammarus and Physella, and avoidance of Dipterans, is consistent with studies in other regions (Cada, Loar, Sale 1987;Pender and Kwak 2002;Fochetti et al 2003;Johnson et al 2007;Sanchez-Hernandez et al 2011), although Pender and Kwak (2002) found positive selection for Chironomidae among age-0 trout. Physella did not constitute a high proportion of either prey availability or prey consumed, but brown trout consistently favored Physella in the benthos and drift.…”
Section: Broad Patternssupporting
confidence: 89%
“…As has been documented in the literature on this subject, the spawning time in brown trout occurs during the autumn-winter period (Hobbs 1937;Needham et al 1945;Horton 1961;Thomas 1964;Hopkins 1970). Some more recent reports also indicate similar spawning periodicity (Pender and Kwak 2002;Alp et al 2003;Estay et al 2004;Rubin et al 2005;Arslan and Aras 2007).…”
Section: Discussionsupporting
confidence: 54%
“…The reproductive traits of brown trout have been described in geographically different populations previously (Hegge et al 1991;Crisp 1994;Sorensen et al 1995;Garcia-Vazquez et al 2001;Nicola and Almodovar 2002;Pender and Kwak 2002;Alp et al 2003;Estay et al 2004;Olsen and Vollestad 2005;Rubin et al 2005;Arslan and Aras 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The age at which the farmed fish matured did not differ from natural conditions (TAUBE, 1976;LUSK, 1968a). Reproduction of the farmed fish annually occurred in November, which was the usual period under conditions corresponding to this latitude (PENDER and KWAK, 2002). The reproductive period of the farmed fish corresponded with that of the reference wild population.…”
Section: Discussionmentioning
confidence: 89%